Injectable hydrogels with high drug loading through B–N coordination and ROS-triggered drug release for efficient treatment of chronic periodontitis in diabetic rats. (March 2022) - Zhao, Xiaodan; Yang, Yuxuan; Yu, Jing; Ding, Rui; Pei, Dandan; Zhang, Yanfeng; He, Gang; Cheng, Yilong; Li, Ang
Abstract: The clinical management of chronic periodontitis with diabetes mellitus (CPDM) is a long-standing thorny issue. The excessive production of reactive oxygen species (ROS) is one of the important implications in CPDM. In the present study, oxidized dextran (OD) and phenylboronic acid-functionalized poly (ethylene imine) (PBA-PEI) were used to develop a novel injectable local drug delivery system (LDDS) which could simultaneously improve drug loading efficiency (doxycycline (Doxy) and metformin (Met)) through B–N coordination and achieve ROS-triggered drug release locally. The injectable LDDS exhibited appropriate adhesiveness to gingival tissue, good biocompatibility, and remarkable antibacterial effect against S. aureus, E. coli, and P. gingivalis. Furthermore, the favorable synergistic effect of Doxy and Met was also verified in vivo in a CPDM rat model through the morphometry and histological observations of alveolar bone, immunohistochemistry staining, and the detection of the expression level of immune-inflammatory mediators in gingival tissue. The results show that the double drug-loaded PBA-PEI/OD hydrogel, as a novel promising therapeutic agent, may be a favorable potential candidate for the CPDM management in the dental clinic.